An Analytical Study on the Awareness Level of NBFC Time Depositors Regarding Deposit Terms and Conditions - Voruganti, Kiran Kumar (Journal of Global Economy, Business and Finance, 2025)
This study examines the awareness levels of NBFC fixed depositors concerning the terms and conditions outlined in fixed deposit application forms. Using a sample from a select locality in Raipur City, the study evaluates depositor knowledge on various aspects such as deposit period, tax deduction, and premature withdrawal. The findings reveal varying levels of awareness among depositors, with implications for investor education and NBFC practices.